Case Report: Successful Control of Pulmonary Metastatic Pheochromocytoma With Iodine-125 Seed Implantation - Shi, Hongbing; Wang, Chao; Qiang, Weiguang; Sun, Bai; Wang, Hao; Yuan, Ye; Hu, Wenwei (Frontiers in Endocrinology, 2021)
Pheochromocytoma with lung metastases is rare in clinics, and the prognosis of metastatic pheochromocytoma is generally poor. In this case, a 57-year-old woman who presented with hypertension and palpitations was diagnosed with left adrenal pheochromocytoma with lung metastasis in 2010. The patient received left adrenalectomy for pheochromocytoma 10 years ago, but pulmonary lesions had significant progression 7 years ago. The patient was treated with iodine-125 (125I) seed implantation for pulmonary lesions. All of the 5 pulmonary lesions achieved partial response 6 months later, further shrank 1 year later, and were successfully controlled for 7 years. This case indicated that 125I seed implantation could be an alternative local therapy for metastatic pheochromocytoma in the lung.